2015
DOI: 10.1186/s13046-015-0157-2
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of the sesquiterpene lactone, EPD, with cisplatin and paclitaxel in ovarian cancer cells

Abstract: BackgroundOvarian cancer remains still the leading cause of death of gynecological malignancy, in spite of first-line chemotherapy with cisplatin and paclitaxel. Although initial response is favorably, relapses are common and prognosis for women with advanced disease stays poor. Therefore efficacious approaches are needed.MethodsPreviously, an anti-cancer agent, EPD exhibited potent cytotoxic effects towards ovarian cancer and not towards normal cells. Cell viability and cell cycle analysis studies were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Therefore, it is very important to get to know the mechanisms that determine drug resistance. However, it is cisplatin that, despite the numerous side effects, is the most often used chemotherapeutic agent [33]. Ineffective apoptosis can be the cause of chemoresistance of cancer cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very important to get to know the mechanisms that determine drug resistance. However, it is cisplatin that, despite the numerous side effects, is the most often used chemotherapeutic agent [33]. Ineffective apoptosis can be the cause of chemoresistance of cancer cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…4B); for these drug interactions, a simplified Bliss independence model was used, 22 and the results described were similar to other low passage ovarian cancer cell lines. 21 Stordal et al 5 studied cytotoxicity of olaparib in 20 ovarian cell lines and concluded that further research is needed to determine which patients who are BRCA1/2 wild type will benefit from treatment with PARP inhibitors. After a successful cytoreductive operation in 2013, patient OVCA-TR3 was treated with a combination of platinum/paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the observed viability after combination treatment is lower than the expected viability, synergistic drug interaction is found (Bliss independence model). 21,22 Hardly any effects were noted for OVCA-TR3.2 with cisplatin alone, but clear synergism could be shown for the combination of cisplatin and EPD. Synergism was found for the combination EPD/paclitaxel only in the cell line OVCA-TR3.3 (P = 0.030).…”
Section: In Vitro Cytotoxicitymentioning
confidence: 96%
See 2 more Smart Citations